UPACARA RITUAL BELIENT SENTIU DAYAK BENUAQ DI KAMPUNG PONAK KECAMATAN SILUQ NGURAI KABUPATEN KUTAI BARAT, KALIMANTAN TIMUR - Nessy Nessy; Nur Rokhim (Greget, 2019)
This paper describes the Ritual Belient Dayak Benuaq Ritual Ceremony in Kampung Ponak, Siluq Ngurai District, West Kutai Regency. This writing originated from the writer’s attention to the arts in East Kalimantan, especially in the village of Ponak, especially in the Benuaq Dayak tribe which still holds close to customs amidst the advancing era and rapidly developing medical science. BelientSentiu ritual ceremony in Ponak village is held when there are people who experience pain outside the medical. Rituals are carried out at night before midnight, according to the community if the ritual is carried out before midnight, the presence of ancestral spirits is more easily felt, and allows ritual performers to be able to communicate well with the spirits of the ruler of the upper world and the ruling spirit of the underworld. has a function that can meet the needs of the Benuaq Dayak community. In this ritual there is the Belient Sentiu dance which is a description of ceremonial activities related to the prevailing customary norms and belief in ancestral spirits. Tonyoi Dayak tribe and Benuaq Dayak tribe.ȱ Keywords:ȱǰȱȱ¢ȱǰȱȱǯ